POTENSI WISATA KAWASAN PESISIR DESA KUALA TRANG KABUPATEN NAGAN RAYA - Amirul Haq; Suldarajat Suldarajat; Abzalul Fikri; Ragil Hasyimi; Nafisah Eka Puteri (Universitas Teuku Umar, 2025)
Kuala Trang in Nagan Raya Regency has significant coastal natural tourism potential, but it has not been optimally utilized for community welfare. This study aims to analyze local resource-based community empowerment strategies to develop a sustainable tourism village. The research method uses qualitative and quantitative approaches to examine supply (through observation and interviews) and demand (through questionnaires of potential tourists). The results show that although the community is very supportive (86%) and the natural scenery is very potential (score 3.86), this destination has critical weaknesses in the institutional aspects (score 1.07), amenities, active attractions, and promotion. Therefore, an integrative empowerment model is formulated that synergizes institutional strengthening (Pokdarwis), community capacity development, the creation of experience-based tourism packages, and digital marketing. The strategic implications emphasize multi-stakeholder collaboration, where the village and district governments act as facilitators and regulators, while the community acts as the main organized actor to create sustainable and equitable tourism.